2014
DOI: 10.1093/ntr/ntu098
|View full text |Cite
|
Sign up to set email alerts
|

Switching Between Menthol and Nonmenthol Cigarettes: Findings From the U.S. Cohort of the International Tobacco Control Four Country Survey

Abstract: While overall switching rates were low, the percentage who switched from menthol to nonmenthol was significantly higher than the percentage who switched from nonmenthol to menthol. An asymmetry was seen in patterns of switching such that reverting back to menthol was more common than reverting back to nonmenthol, particularly among Black smokers.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
35
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(37 citation statements)
references
References 30 publications
2
35
0
Order By: Relevance
“…Extant studies have suggested that menthol use preference is established early on, with little switching for either women or men, with estimates of switching among youth around 6% (17). Although not included in this review, Kasza and colleagues reported a similar finding with perhaps even lower switching among adults in the U.S (16). …”
Section: Discussionmentioning
confidence: 65%
“…Extant studies have suggested that menthol use preference is established early on, with little switching for either women or men, with estimates of switching among youth around 6% (17). Although not included in this review, Kasza and colleagues reported a similar finding with perhaps even lower switching among adults in the U.S (16). …”
Section: Discussionmentioning
confidence: 65%
“…Nevertheless, switching between menthol and non-menthol cigarettes does not appear to be common. 37 Fourth, this study defined successful smoking cessation using ≥3 months criterion following previous studies, 14,23,24 as literature indicates that 65% of quitters relapse within the first 3 months. 38 While successful abstinence of ≥6 months has been a commonly used criterion in clinical trials and longitudinal studies, 12,13,[16][17][18] previous cross-sectional studies have used the criterion of ≥0 month, 15 ≥1 month, 39 ≥3 month, 14 and ≥6 months.…”
Section: Discussionmentioning
confidence: 99%
“…Smokers of menthol CCs were not eligible for this study to avoid inducing changes in smoking patterns which are likely to result from switching current smoker of menthol CCs to a nonmenthol product, as the prevalence of switching between menthol and nonmenthol cigarettes is low. 14 …”
Section: Methodsmentioning
confidence: 99%